Student’s Numerical Ability on Minimum Competency Assessment in Indonesia: Focusing on Data and Uncertainly Problems (Journal of Didactic Studies, 2023)
This study aims to describe students' numeracy ability in solving math problems on data content and uncertainty based on the Minimum Competency Assessment (AKM) in terms of students' initial abilities at SMPN 1 Parepare. The subjects of the study were 6 students: 2 students with low initial ability, 2 students with medium initial ability, and 2 students with high initial ability. 6 subjects are grade IX students at SMPN 1 Parepare for the 2022/2023 school year. The results showed that (1) Students with low initial mathematical ability only met three numeracy indicators. Thus, students with a low initial mathematics ability category are at the competency level of "Need for Special Intervention", (2) Students with moderate initial mathematics ability are only able to meet four numeracy indicators. Thus, students with the category of initial ability in mathematics are at the level of competence "Capable", (3) Students with early ability in high mathematics can meet all indicators of numeracy ability. Thus, students with the category of early ability of high mathematics are at the level of competence "Proficient”.